LEGAL ASPECTS OF FINANCIAL ANALYSIS IN AGRIBUSINESS COMPANIES IN SERBIA - Majstorović, Aleksandar; Miloradić, Jova; Andžić, Slobodan; Andžić, Rosa; Divac, Goran; Aničić, Anđelka (Economics of Agriculture, 2018)
As a company is a living organism, its growth and development depends on the adequacy of planning, control and analytical procedures that are in use in all aspects of their own business. Under such conditions, the accounting analysis involves primarily adequate monitoring already included in the displayed information contained in the fnancial statements and in particular the analysis of data that are essential to the operation of any enterprise. Knowledge and the application of modern accounting analysis will give to the agribusiness company management a wide range of options in terms of uninterrupted growth and development of the agribusiness company in accordance with a pre-designed and presented vision and mission.